2021
DOI: 10.1002/adhm.202101565
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐BCMA Immuno‐NanoPET Radiotracers for Improved Detection of Multiple Myeloma

Abstract: Current clinical imaging modalities for the sensitive and specific detection of multiple myeloma (MM) rely on nonspecific imaging contrast agents based on gadolinium chelates for magnetic resonance imaging (MRI) or for 18 F-FDG-directed and combined positron emission tomography (PET) and computed tomography (CT) scans. These tracers are not, however, able to detect minute plasma cell populations in the tumor niche, leading to false negative results. Here, a novel PET-based anti-BCMA nanoplatform labeled with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…[ 18 F]fluorodeoxyglucose (FDG), has been the leading nuclear medicine tracer for oncologic studies, as demonstrated by its wide availability and frequent use (1). Of note, as compared to solid tumors, in hematological malignancies, 18 F-FDG-PET/CT remains the mainstay for imaging of extramedullary infiltration, relapse and assessment of inflammatory activity in leukemia as well as in 18 F-FDG-avid lymphoma (2). There is increasing evidence of superior accuracy when nuclear imaging is synergized with liquid biopsies (3).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 18 F]fluorodeoxyglucose (FDG), has been the leading nuclear medicine tracer for oncologic studies, as demonstrated by its wide availability and frequent use (1). Of note, as compared to solid tumors, in hematological malignancies, 18 F-FDG-PET/CT remains the mainstay for imaging of extramedullary infiltration, relapse and assessment of inflammatory activity in leukemia as well as in 18 F-FDG-avid lymphoma (2). There is increasing evidence of superior accuracy when nuclear imaging is synergized with liquid biopsies (3).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical and functional imaging play a forefront role in the detection of minimal residual disease, relapse and therapy response as well (10). 18 F-FDG-PET/CT works adequately in patients manifesting with 18 F-FDG-avid myeloma lesions (11). Despite its frequent use in the clinic, a known limitation of 18 F-FDG-PET in MM is the inconsistent expression of the glucose transporter, GLUT-1, and the hexokinase-2 enzyme in myeloma cells (12).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations